Loch Ness uncovered : media, misinformation, and the greatest monster hoax of all time - Siegel, Rebecca (Astra Young Readers, an imprint of Astra Books for Young Readers, 2024)
"Loch Ness Uncovered is an extensively researched, myth-busting account of the world's most famous monster hoax-the Loch Ness Monster-and a cautionary tale on the dangers of misinformation"--